(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
Titles were an integral part of the Islamic civilization in every era, and a title indicating the approach of each caliph, and a standard for understanding peoples, as titles were distinguished in the first Abbasid era by strength and luxury, so they were called caliphs as a kind of appreciation until they took the character of praise and praise. To impart a religious character related to prophecies and epics, such as the title of Al-Hadi and Al-Mahdi, and were used to honor and venerate, such as the title of Al-Rashid, and titles had a great role in serving politics, showing the power and prestige of the Caliphate to terrorize enemies such as the title The Butcher and Mansour, and thus the titles performed their political and intellectual function in accordance with the level of social and cultural developments For the Arab and Islamic world at that time.